Habitat types mapping using remote sensing techniques in Cyprus - Makri, Despina; Kalogirou, Eleftheria; Iqbal, Muhammad Amjad; Hadjimitsis, Diofantos G.; Mettas, Christodoulos (My University, 2025)
Oceans cover 75% of the Earth's surface and account for 99% of the planet's living space by volume. They are home to around 200,000 known species, with Posidonia oceanica meadows being among the oldest. These habitats are very important coastal ecosystems, providing vital services such as habitat for marine life, coastal protection, and oxygen generation. Despite their importance, seagrass meadows, including Posidonia oceanica, face significant threats, including degradation and loss, with slow regeneration rates. As a result, their monitoring and conservation are essential for maintaining biodiversity and the health of marine ecosystems. This study presents an innovative approach for mapping and monitoring seagrass meadows in western Cyprus using the Google Earth Engine (GEE) platform. Leveraging freely available satellite data from the Copernicus Program, we demonstrate how Earth observation tools can be utilized to map the spatial extent of seagrass meadows and other significant habitat types. This approach supports the monitoring efforts of the European Union’s conservation frameworks and aligns with the United Nations' Sustainable Development Goal (SDG) 14, focusing on the conservation of marine life. The integration of GEE for seagrass mapping offers a scalable and efficient method to track habitat changes, contributing to more effective conservation strategies and ensuring the sustainable use of coastal ecosystems.
Keywords: remote sensing; habitat mapping; google earth engine; seagrass